MEASURING PROFICIENCY IN STANDARD INDONESIAN FOR ENGGANO SPEAKERS - Rindu Parulian Simanjuntak (Masyarakat Linguistik Indonesia, 2014)
The main purpose of study described in this paper was to measure the proficiency of Standard Indonesian spoken in Enggano Island, Bengkulu Province, Indonesia. Enggano is spoken in six villages: Malakoni, Apoho, Meok, Ka’ana, Kayapu and Banjar. Of these, two villages — Meok and Ka’ana — were selected as research sites for collecting data. The instruments used were the Indonesian Sentence Repetition Test (ISRT) (Hanawalt 2008) and a set of bilingualisms questionnaire. The results show an average bilingual proficiency in Standard Indonesian of level 2 on the ILR scale (Interagency Language Roundtable 2007) for Enggano speakers, which indicates an ability to use Indonesian limited to particular situations and domains. The analysis also shows that bilingual proficiency in Enggano varies on average between males and females and is influenced by education and age, but not by the other factors investigated. This means that bilingual proficiency in Standard Indonesian for Enggano speakers is largely the result of continuing on to higher levels of education. Even though the average proficiency of Enggano speakers in Standard Indonesian is at level 2, the attitudes of most Enggano speakers towards both the Indonesian language and the local vernacular language are strongly positive.